Board of Directors and Risk-taking Behavior of Islamic Banks in South East Asia - Faaza Fakhrunnas; Zulkufly Ramly (Institute for Research and Community Empowerment (LPPM TAZKIA), 2016)
Board of Directors (BODs) and Shariah Supervisory Board (SSB) have a pivotal role to manage Islamic banks in Southeast Asia. The decision made by the BODs and SSB will directly affect to the risk-taking behavior performed by Islamic bank. This study aims to investigate the relationship among BODs, SSB and risk-taking behavior of Islamic banks in Southeast Asia. Adopting random effect model, this research utilizes 24 Islamic banks in Southeast Asia which observe over six periods from 2009 to 2014. By using unbalanced panel data, the result of the study reveals that independent director influences the risk-taking behavior positively while Shariah Supervisory Board (SSB) affects it negatively. In addition, Board size has positive effect to the credit risk but negative to z-score.